Performance And Prospect Analysis Indonesian Coffee Commodity In Domestic And International Markets - Saputera, Denny; Moenardi, Dwi Fauziansyah; Muttaqin, Rizqi; Dewi, Rina Ariyanthi; Hawari, Hasbi (CENTRAL ASIA AND THE CAUCASUS, 2022)
The plantation sector contributed 3.27% to GDP out of a total of 25.71% in the agricultural sector, although forestry and fisheries were superior in order. In the coffee plantation sector, it is one of the leading commodities that play a role in Indonesia's economic growth in obtaining foreign exchange. In Indonesia, most of the coffee exported dominates in the form of raw (coffee beans), of course, this is an added value and advantage in the final product by importing countries which can determine the selling price, as is the case in Indonesia which is of course the main commodity. from our country is unstable and dependent on consumer countries. This study uses secondary and primary data. The design in this study uses a qualitative descriptive research design, for the object of research comes from the suitability of Indonesian coffee export and import data. Our country, Indonesia, should strive to increase domestic production, provide policies that can stimulate farmers to be able to increase domestic production, this arises from opportunities from the continued increase in imports of coffee beans.